Prebiotic Membranes and Micelles Do Not Inhibit Peptide Formation During Dehydration. (20th December 2021) - Cohen, Zachary R.; Kessenich, Brennan L.; Hazra, Avijit; Nguyen, Julia; Johnson, Richard S.; MacCoss, Michael J.; Lalic, Gojko; Black, Roy A.; Keller, Sarah L.
Abstract: Cycles of dehydration and rehydration could have enabled formation of peptides and RNA in otherwise unfavorable conditions on the early Earth. Development of the first protocells would have hinged upon colocalization of these biopolymers with fatty acid membranes. Using atomic force microscopy, we find that a prebiotic fatty acid (decanoic acid) forms stacks of membranes after dehydration. Using LC‐MS‐MS (liquid chromatography‐tandem mass spectrometry) with isotope internal standards, we measure the rate of formation of serine dipeptides. We find that dipeptides form during dehydration at moderate temperatures (55 °C) at least as fast in the presence of decanoic acid membranes as in the absence of membranes. Our results are consistent with the hypothesis that protocells could have formed within evaporating environments on the early Earth. Abstract : Dried dispersions of decanoic acid vesicles produce stacks of membranes. In the presence of the dried membranes, serine‐ethyl‐esters are converted into dipeptides at a rate that is at least as fast as in the absence of membranes. Our results enhance the plausibility that protocells (which would have colocalized membranes, RNA, and peptides) could have developed in evaporating environments on the prebiotic Earth.